A Computational Study of Vicinal Fluorination in 2, 3‐Difluorobutane: Implications for Conformational Control in Alkane Chains. Issue 4 (21st November 2014) - Fox, Stephen J.; Gourdain, Stephanie; Coulthurst, Anton; Fox, Clare; Kuprov, Ilya; Essex, Jonathan W.; Skylaris, Chris‐Kriton; Linclau, Bruno
Abstract A comprehensive conformational analysis of both 2, 3‐difluorobutane diastereomers is presented based on density functional theory calculations in vacuum and in solution, as well as NMR experiments in solution. While for 1, 2‐difluoroethane the fluorine gauche effect is clearly the dominant effect determining its conformation, it was found that for 2, 3‐difluorobutane there is a complex interplay of several effects, which are of similar magnitude but often of opposite sign. As a result, unexpected deviations in dihedral angles, relative conformational energies and populations are observed which cannot be rationalised only by chemical intuition. Furthermore, it was found that it is important to consider the free energies of the various conformers, as these lead to qualitatively different results both in vacuum and in solvent, when compared to calculations based only on the electronic energies. In contrast to expectations, it was found that vicinal syn‐difluoride introduction in the butane and by extension, longer hydrocarbon chains, is not expected to lead to an effective stabilisation of the linear conformation. Our findings have implications for the use of the vicinal difluoride motif for conformational control.